Why communication is vital during a cyber-attack. Issue 3 (March 2017) - Hawkins, Nick
Abstract : Cyber-attacks are a constant threat to organisations. However, cloud-based communications platforms can help an organisation improve emergency communications and more effectively recover from the effects of a attack.